The prionlike domain of FUS is multiphosphorylated following DNA damage without altering nuclear localization - Rhoads, Shannon N. (Mol Biol Cell, 2018)
FUS (fused in sarcoma) is an abundant, predominantly nuclear protein involved in RNA processing. Under various conditions, FUS functionally associates with RNA and other macromolecules to form distinct, reversible phase-separated liquid structures. Persistence of the phase-separated state and increased cytoplasmic localization are both hypothesized to predispose FUS to irreversible aggregation, which is a pathological hallmark of subtypes of amyotrophic lateral sclerosis and frontotemporal dementia. We previously showed that phosphorylation of FUS’s prionlike domain suppressed phase separation and toxic aggregation, proportionally to the number of added phosphates. However, phosphorylation of FUS’s prionlike domain was previously reported to promote its cytoplasmic localization, potentially favoring pathological behavior. Here we used mass spectrometry and human cell models to further identify phosphorylation sites within FUS’s prionlike domain, specifically following DNA-damaging stress. In total, 28 putative sites have been identified, about half of which are DNA-dependent protein kinase (DNA-PK) consensus sites. Custom antibodies were developed to confirm the phosphorylation of two of these sites (Ser-26 and Ser-30). Both sites were usually phosphorylated in a subpopulation of cellular FUS following a variety of DNA-damaging stresses but not necessarily equally or simultaneously. Importantly, we found DNA-PK–dependent multiphosphorylation of FUS’s prionlike domain does not cause cytoplasmic localization.